Social status of women in Ancient Sparta - I. A. Lohvynenko; Ye. S. Lohvynenko (Law and Safety)
The factors that determined the peculiarities of the social status of women in Ancient Sparta have been identified and analysed. It has been demonstrated that the establishment of community control over private life, namely: strict regulation of marriage and family relations, the compulsory nature of specific general education, which started for girls at the age of eight and lasted until marriage, determined that the national interests of women became a priority and dominated family values. It has been found that in Sparta, as in other polities of ancient Greece, childbearing was considered the most important function of women, as the offspring were to continue family traditions and take care of their elderly parents, conduct religious rites, etc. Only male children were seen as future citizens and defenders of the polis. In Lacedaemon, motherhood acquired a more accentuated meaning and was understood as service to the state. It became the basis of marriage and family relations, where polyandry was perceived as the norm. The Spartan woman was socially active. She was a direct participant in religious festivals and rituals, sports competitions. She publicly ridiculed the bachelors and cowards. If her own son turned out to be a coward, she could kill him herself. A mother did not bear any legal responsibility for the murder of a cowardly son. The economic rights of Spartans, which other women in ancient Greece did not have, have been investigated. Due to her husband’s military service, a Lacedaemonian woman managed not only his oikos, but also his cleris. Polyandry allowed a woman to unite two or more “houses” under her control and thus increase her influence in society. It has been noted that a strong economic foundation allowed wealthy women to have more freedom in society and even influence those in power in making responsible political decisions. With the loss of Messenia, women lose their economic freedom. The social status of women also changes, as they become more subordinate to men. It has been argued that in Sparta, the state minimised the private life of spouses. Under such conditions, a woman was socially active, knew the inner life of the polis well, and understood the foreign policy priorities of the state. She acted as a motivator and guide of Spartan ideology for the men of her family. And in this way, the Lacedaemonian woman was significantly different from other women in ancient Greece.